Enhancing Drought Tolerance of Wheat (Triticum aestivgum L.) Through Foliar Application of Proline and L-Triptophan: Proline and L-Triptophan Induced Drought Tolerance in Wheat - Shabir, Asad; Saqib, Muhammad; Ahmad, Maqshoof; Latif, Muhammad; Bukharia, Syed Asad Hussain; Ahmad, Muhammad Qadir; Dawood, Muhammad; Rashid, Muhammad (Biological Sciences - PJSIR, 2020)
Limited water availability is one of the important abiotic factor affecting yield of wheat crop. Exogenous application of osmolytes is an important factor in reducing the stress due to water shortage. Keeping in view the role of proline and L-tryptophan (L-TRP) in stress alleviation, a study was carried out at the agricultural research area of the University College of Agriculture and Environmental Sciences, The Islamia University of Bahawalpur, Pakistan, during winter 2015-2016 to evaluate the impact of foliar applied proline and L-TRP on growth and photosynthetic efficiency of wheat grown under limited moisture supply. Drought stress was applied in three levels (I1 = control, I2 = drought stress at tillering stage and I3 = drought stress at grain filling stage) while, foliar application of proline and L-TRP was done in six levels [T1 = control; T2 = proline (10 mM); T3 = proline (20 mM); T4 = L-TRP (10-4 M); T5 = L-TRP (10-4 M) + proline (10 mM) and T6 = L-TRP (10-4 M) + proline (20 mM)]. The experimental results revealed that growth and photosynthetic efficiency of wheat were decreased due to reduced water supply. However, exogenously applied proline and L-TRP considerably ameliorated the effect of drought stress. Combined application of L-TRP (10-4 M) and proline (20 mM ) showed better results and induced tolerance to drought stress, in comparison with other treatments. Foliar application of proline and L-TRP also enhanced the photosynthetic rate which might be related with the improved photosynthetic pigments. Overall, exogenously applied proline and L-TRP mitigated the adverse effects of moisture deficit on growth and photosynthetic efficiency of wheat crop.